Social ideology and taxes in a differentiated candidates framework - Stefan Krasa; Mattias Polborn (Center for Economic Studies and ifo Institute (CESifo), 2011)
How does ideological polarization on non-economic matters influence the size of government? We analyze this question using a differentiated candidates framework: Two office-motivated candidates differ in their (fixed) ideological position and their production function for public goods, and choose which tax rate to propose. We provide conditions under which a unique equilibrium exists. In equilibrium, candidates propose different tax rates, and the extent of economic differentiation is influenced by the distribution and intensity of non-economic preferences in the electorate. In turn, the extent of economic differentiation influences whether parties divide the electorate primarily along economic or social lines.
Keywords: D72; 330; differentiated candidates; policy divergence; ideology; Ideologie; Public Choice; Staatsquote; Steuerpolitik; Öffentliches Gut; Theorie